Etnologi bortom humanismen - Eddy Nehls (Kulturella Perspektiv, 2008)
The article tries to introduce a new thinking in ethnology, a post human perspective. The starting point of the discussion is a reflection on the many battles that has been fought among ethnologists during the 20th century about how to best understand the concept of culture. What is a human being is a good question to start with, if one wants to take on a post human perspective and in this article the answer is (partly) given by Gregory Bateson who says, in the title on one of his most famous books, that Mind and Nature is a necessary unity. The boundary between humans and non-humans is highly problematic because it is restraining the possibility to work in an unbiased fashion. Some main concept of Actor-Network-Theory (ANT) is then introduced as one of many possible ways to work with a post human perspective. Actor is understood as everything that can make a difference. Humans are only one actor among others whom all are connected in a network as the acronym ANT indicates. Working with such analytical tools is about finding traceable connections between actors. Society or culture understood in this way cannot be the explanation to anything; it is on the contrary what should be explained. One of the most important points that are made in the article is that this is not fundamentally new thoughts to ethnologists.